2012
DOI: 10.1002/jmri.23607
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis: An intravoxel incoherent motion (IVIM) study

Abstract: Purpose: To characterize longitudinal changes in molecular water diffusion, blood microcirculation, and their contributions to the apparent diffusion changes using intravoxel incoherent motion (IVIM) analysis in an experimental mouse model of liver fibrosis. Materials and Methods:Liver fibrosis was induced in male adult C57BL/6N mice (22-25 g; n ¼ 12) by repetitive dosing of carbon tetrachloride (CCl 4 ). The respiratorygated diffusion-weighted (DW) images were acquired using single-shot spin-echo EPI (SE-EPI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 78 publications
6
88
0
Order By: Relevance
“…Categorical variables were evaluated by v 2 and Fisher's exact test. For statistical analysis, necro-inflammatory activity score was grouped as none (score 0), mild (scores 1-6), moderate (scores 7-12), and severe inflammation (scores [13][14][15][16][17][18]. The Ishak fibrosis staging was categorized into none (F0), mild to moderate fibrosis (F1-F3), and marked fibrosis/cirrhosis (F4-F6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Categorical variables were evaluated by v 2 and Fisher's exact test. For statistical analysis, necro-inflammatory activity score was grouped as none (score 0), mild (scores 1-6), moderate (scores 7-12), and severe inflammation (scores [13][14][15][16][17][18]. The Ishak fibrosis staging was categorized into none (F0), mild to moderate fibrosis (F1-F3), and marked fibrosis/cirrhosis (F4-F6).…”
Section: Discussionmentioning
confidence: 99%
“…The IVIM model allows separating the liver signal intensity changes due to true molecular diffusion from those related to perfusion within the tissue. Recently, it has been proposed that the IVIM model, and particularly the perfusion-related parameters D* and f, would be more advantageous to evaluate liver fibrosis than conventional ADC measurements [5,[13][14][15][16][17][18][33][34][35]. However, the influence of liver inflammation, steatosis and siderosis on liver values has to be considered in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of diethylnitrosamineinduced liver fibrosis, Zhang et al (57) reported that PF values decreased significantly with the increasing fibrosis level; but Dslow was poorly correlated with fibrosis level. In a carbon tetrachloride induced rat liver fibrosis model, Chow et al (58) reported that as liver fibrosis progressed, Dslow and Dfast decreased, however there was no change in PF. Joo et al (59) reported that PF was significantly lower in rabbits with nonalcoholic fatty liver disease than in those significantly lower in fibrotic livers.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 99%
“…Both diffusion and perfusion can be quantified or estimated separately by multi-b values according to a bi-exponential model, including D, f, and D*, which represent the pure diffusion coefficient, perfusion fraction, and pseudodiffusion coefficient, respectively. Recently, IVIM has become popular and has been applied routinely in the human body, mostly to evaluate therapeutic response (5,6), in chronic disease assessment (7,8), and for lesion detection and characterization (9,10). One of the most conspicuous advantages of IVIM is that it does not require contrast medium injection.…”
mentioning
confidence: 99%